Two new records of Heteroptera species in Slovenia - Gogala, Andrej (Acta entomologica slovenica (Ljubljana), 2010)
Stephanitis pyrioides (Scott, 1874), an introduced species, and Deraeocoris schach (Fabricius, 1781) are two species of Heteroptera, found in Slovenia forthe first time in 2009. The data on the finds are presented.
Keywords: entomologija; favna; Heteroptera; Slovenia; Slovenija